Dual-functional gas hydrate inhibition of tetramethylammonium chloride for carbon dioxide-methane mixed gas systems - Moujdin, I.A. (Elsevier Ltd, 2021)
The present work deals with evaluating the dual-functional gas hydrate impact of tetramethylammonium chloride (TMACl) in the presence of different CO2-CH4 content mixed gas hydrate systems (30CO2 + 70CH4, 50CO2 + 50CH4, and 70CO2 + 30CH4). A custom-made high-pressure gas hydrate reactor was used to acquire the temperatureâpressure loops for the studied systems in the absence/presence of different concentrations of aqueous TMACl solutions via T-Cycle and isochoric constant cooling method for both THI and KHI investigations, respectively. The electrolyte-based thermodynamic model was also applied to validate the obtained HLwVE results for all the studied systems. The obtained results revealed that TMACl acts dual-functional (thermodynamic and kinetic) hydrate inhibitor for high CO2 content gas systems. The increased concentration of TMACl induces more shifts in HLwVE data with maximum variation attained at10 wt concentration up to 1.46 K for a high CO2 content methane system owing to the increased hydrogen bonding ability of TMACl. Moreover, TMACl delayed the hydrate formation up to 1.4 and1.5 folds for 274.0 and 277.0 K conditions for high CO2 content mixed gas systems. Moreover, the applied electrolyte-based model could predict the HLwVE data of TMACl in the presence of a mixed gas system within the AAE value of 0.1 for all the studied mixed gas systems. Furthermore, the KHI performance of TMACl was also compared with commercial inhibitor, i.e., polyvinyl pyrrolidone (PVP), and obtained comparable results. Therefore, the acquired dual-functional results (THI = 1.46 K, KHI = 1.5-fold delay) signpost that TMACl can efficiently work as a potential dual-functional hydrate inhibitor for CO2 enriched mixed gas systems. Â© 2021 Elsevier Ltd